(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Mental health consists of the absence of mental disorders and the presence of mental well-being. However, currently, psychiatric care focuses mainly on mental disorders and to a lesser extent on mental well-being. Yet, people with personality problems often have very low well-being scores. In order to work on sustainable mental health, attention must be paid to both mental complaints and well-being, and this is achieved by promoting psychological adaptation.